2015
DOI: 10.1189/jlb.5mr0315-127r
|View full text |Cite
|
Sign up to set email alerts
|

The future of murine sepsis and trauma research models

Abstract: Recent comparisons of the murine and human transcriptome in health and disease have called into question the appropriateness of the use of murine models for human sepsis and trauma research. More specifically, researchers have debated the suitability of mouse models of severe inflammation that is intended for eventual translation to human patients. This mini-review outlines this recent research, as well as specifically defines the arguments for and against murine models of sepsis and trauma research based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
102
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 90 publications
(106 citation statements)
references
References 64 publications
1
102
0
3
Order By: Relevance
“…Interestingly, the genomic responses to these various stressors were very similar in humans, but not in mice (38). One explanation is that the current murine models are poor representations of the human condition (9,10). In support of that conclusion, we have reported that increasing injury severity in a murine trauma model produced a modest but significant improvement in correlation between patterns of human and murine gene expression (16).…”
supporting
confidence: 68%
See 3 more Smart Citations
“…Interestingly, the genomic responses to these various stressors were very similar in humans, but not in mice (38). One explanation is that the current murine models are poor representations of the human condition (9,10). In support of that conclusion, we have reported that increasing injury severity in a murine trauma model produced a modest but significant improvement in correlation between patterns of human and murine gene expression (16).…”
supporting
confidence: 68%
“…In contrast, the failure of murine models to recapitulate the human response may well be due to the nature of the injury models and time periods selected (10,16). Although the response to a 30% burn injury, administration of endotoxin, and hemorrhagic shock with a laparotomy were transcriptomically dissimilar, it can be argued that these murine models are suboptimal representations of human infection and injury (10).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…However, major differences in the nature of the transcriptome responses depend on the model used [105], and well-recognized differences between humans and mice may limit the application of findings across species. This justifies direct observations in humans [106]. Most recently, two important genome-wide gene expression studies have provided insights into the molecular pathways activated in newborns with severe infections [88,107].…”
Section: Lessons From Neonatal Mouse Modelsmentioning
confidence: 99%